PENGAWASAN BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) MEWUJUDKAN NETRALITAS APARATUR SIPIL NEGARA (ASN) PADA PEMILIHAN KEPALA DAERAH TAHUN 2020 DI KABUPATEN PELALAWAN - Khairunissa, Triarta; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study discusses the supervision carried out by the General Election Supervisory Body (Bawaslu) in maintaining the neutrality of the State Civil Apparatus (ASN) in the 2020 Regional Head Election (Pilkada) in Pelalawan Regency. The neutrality of ASN is a crucial principle in ensuring fairness and transparency in the administration of elections, especially in Pilkada, where ASN is expected to be impartial and not use their position for political purposes. The purpose of this study is to analyze the effectiveness of Bawaslu's supervision of ASN neutrality violations, particularly in various stages of the Pilkada, such as candidate registration, campaigning, and voting. This research uses a qualitative method with data collection techniques in the form of interviews and documentation. The results show that despite Bawaslu's efforts to monitor, violations of ASN neutrality still occur, albeit in small numbers. The contributing factors to these violations include the lack of effective sanctions and the lack of understanding of ASN's role and responsibility in maintaining neutrality. Therefore, stronger strategic steps are needed to increase ASN awareness and understanding and to strengthen inter-agency cooperation in enforcing ASN neutrality violations. Keywords : Supervision, Neutrality, ASN, Pilkada, Bawaslu